Giant cell myocarditis in an older patient – reassessing the threshold for endomyocardial biopsy - Dusík, Milan (ESC Heart Fail, 2020)
Giant cell myocarditis is a rare form of autoimmune myocarditis with high morbidity and mortality that affects mainly middle‐aged adults. We report a case study of a 70‐year‐old man on chronic immunosuppression who presented with sustained ventricular tachycardia and symptoms of acute systolic heart failure, both with poor response to standard measures. A decision to pursue endomyocardial biopsy established the diagnosis of GCM and lead to initiation of immunosuppressive therapy and a favourable outcome. Our case illustrates that a low threshold for endomyocardial biopsy in new onset heart failure can lead to actionable information even in patients of advanced age.